Analisis Yuridis Perlindungan Hukum Perjanjian Dibawah Tangan Berdasarkan Putusan Pengadilan No.161/pdt.g/2011/pn-mdn. (Studi Kasus PT Merim Property dan Cv Rira Karya) - Weriyus Heston Marbun (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2020)
Legal protection for every Indonesian citizens without exception can be found in the 1945 Constitution of the Republic of Indonesia (1945 Constitution), therefore every product produced by the legislature must always be able to provide guarantees of legal protection for all people, even they must be able to capture legal and justice aspirations that develop in society. In the Civil Code article 1233 states, "that an alliance can be formed because of agreement or law". One form of the agreement is an agreement under the hands in the form of contract work agreement.           The results of the case study of PT Merim Property and CV Rira Karya can be seen the weakness of an agreement under the hands, where CV Rira Karya as the plaintiff must have concrete evidence to prove the loss that they experienced in accordance with the agreement under the hands that they agreed upon, where such evidence cannot be given CV Rira Karya so that his lawsuit was rejected by the panel of judges. The legal consequences arising related to the use of an agreement under the hands in the event of a default are that the debtor is required to pay compensation, the creditor may request the cancellation of the agreement through the court and the creditor can request the fulfillment of the agreement, or fulfillment of the agreement accompanied by compensation and cancellation of the agreement with compensation. Keywords: Analysis, Legal Protection, Agreement, Under the Hands